Dampak Pandemi Covid-19 Terhadap Sektor Riil: Telaah, Harapan dan Penentuan Arah Kebijakan Sustainable Development Goals (SDGs) dan Ziswaf - Muhibbul Zibbri; Habibah Awwaliah; Lailussoma Lailussoma; Muhamad Fauzin Nur (Universitas Islam Lamongan, 2021)
Abstract: Covid-19 is a virus that spreads very rapidly and has a clear impact on the areas of human life, such as health, social, economic, and religious perspective. The real impacts occurred in the economic sector are the declined economy due to the physical distancing policy for the community to do activities and the decreased public consumption which resulted in stagnant circulation of money. This is in accordance with the theory of the flow concept, money (property) must continue to flow to ensure that the economy is alive and integrated with one another, so that there is a confluence of economic circulation between the excess and the needy, and vice versa. Objectives that identify and provide recommendations that seek to support the SDG, especially the values that end all forms of society and inequality in communities affected by covid-19. This article uses descriptive qualitative methods using written sources such as the latest news, books, and research journals, as well as interview results that are relevant to the theme raised. The results of this study state that philanthropy can be an effective medium and means of supporting distribution stimulus while at the same time overcoming the impact of the spread of covid-19. This effort is also related to the application of SDG values which are oriented towards poverty alleviation and reduction of victims of malnutrition in the present or future. The suggestion that can be delivered is the cooperation between the community and the government which is assisted by the improvement of the ZISWAF Institution’s performance. It is hoped that it can optimize the realization of philanthropic funds to reduce the economic burden of victims while also applying the value of the Sustainable Development Goals (SDG). Keywords: covid-19, islamic philanthropy, Sustainable Development Goals